Shifting MNE taxation from national to global profits: A radical reform long overdue - McGaughey, Sara L.; Raimondos, Pascalis (Journal of International Business Studies, 2019)
The current “Separate Accounting” taxation of corporations gives governments the right to tax the national incomes of firms operating within their borders. However, multinational and increasingly digital business models beg the question: what is national taxable income? We argue that a radical rethink of the corporate taxation – moving away from a separate taxation of national corporate income to a taxation of global corporate income allocated via “Formula Apportionment” – is long overdue. Global corporate income as a basis for taxation is supported both by recent theoretical developments and corroborating empirical evidence, with the EU and emerging economies including China already considering its adoption. Nor is it new. As we relate, formula apportionment of global corporate income was used a century ago before commercial and political interests promoted separate accounting, thereby providing both precedent and experience to inform its re-adoption.